Synergistic combination of doxorubicin with hydralazine, and disulfiram against MCF-7 breast cancer cell line - Lafi, Zainab; Alshaer, Walhan; Gharaibeh, Lobna; Alqudah, Dana A.; AlQuaissi, Baidaa; Bashaireh, Banan; Ibrahim, Abed Alqader (PLOS ONE, 2023)
Disulfiram and hydralazine have recently been reported to have anti-cancer action, and repositioned to be used as adjuvant in cancer therapy. Chemotherapy combined with other medications, such as those that affect the immune system or epigenetic cell profile, can overcome resistance with fewer adverse effects compared to chemotherapy alone. In the present study, a combination of doxorubicin (DOX) with hydrazine (Hyd) and disulfiram (Dis), as a triple treatment, was evaluated against wild-type and DOX-resistant MCF-7 breast cancer cell line. Both wild-type MCF-7 cell line (MCF-7_WT) and DOX-resistant MCF-7 cell line (MCF-7_DoxR) were treated with different combination ratios of DOX, Dis, and Hyd followed by measuring the cell viability using the MTT assay. Synergism was determined using a combination index, isobologram analysis, and dose-reducing index. The anti-proliferation activity and mechanism of the triple combination were investigated by apoptosis analysis. The results showed a reduction in the IC50 values of DOX in MCF-7_WT cells (from 0.24 μM to 0.012 μM) and MCF-7_DoxR cells (from 1.13 μM to 0.44 μM) when treated with Dis (0.03μM), and Hyd (20μM) combination. Moreover, The triple combination DOX/Hyd/Dis induced significant apoptosis in both MCF-7_WT and MCF-7_DoxR cells compared to DOX alone. The triple combination of DOX, Dis, and Hyd showed a synergistic drugs combination to decrease the DOX dose needed to kill both MCF-7_WT and MCF-7_DoxR cancer cells and enhanced chemosensitivity to DOX.